Quantifying the Extent of Damage in a Moment-resisting Frame Caused by Ground Motions using Normalized Discrete Wavelet Coefficients - Seyyed Meisam Aghajanzadeh; Mohammadreza Mashayekhi (Numerical Methods in Civil Engineering)
The assessment of structures' residual strength and stiffness right after experiencing strong ground motions is a vital concern. Different studies detect seismic damage successfully but assessing extent of the damage have limitations as the damage has been modeled as abrupt change, location of the damage should be known in advance or frequency and stiffness analysis are needed. This study presents a novel method that uses a damage-sensitive parameter to capture the extent of damage that gradually developed caused by earthquakes. It is calculated by the normalized wavelet decomposition. The method quantifies the extent of seismic damage along with the structural performance levels of Immediate Occupancy and Collapse Prevention. The damage-sensitive parameter depends more on earthquake properties than on structure properties. Among PGA, PGA/PGV, and Impulsivity Index (IP), the damage sensitive parameter relates to the Impulsivity Index (IP) of the ground motions. This method only depends on the structural response histories